Diversity and Utilization of Forestry Resources for Enhancing Household Food Security in the Leh Himalaya, India - , F.A. Shah Khan; , M.A. Islam; , A.A. Gatoo; , G.M. Bhat; , A.A. Parrey; , M.R. Bakshi; , Ummar Atta; Chandramolly, (Archives of Current Research International, 2024)
Food resources extracted from forestry landscapes enhance the quality of diets, improve health care, and ensure income diversification for local communities in developing countries. This paper explores the diversity, seasonality, distribution, mode of use, frequency of use, and reliance of forestry food resources on livelihoods in the Leh Himalaya. Data were collected from 185 sample families that were selected from five blocks and nine villages using a multi-stage random sampling procedure. Descriptive statistics were applied to the data analysis. Results revealed that 37 forestry food resources were harvested from 27 herbs, 3 shrubs, and 3 trees belonging to 28 genera and 19 families, and consumed as vegetables (15), fruits (5), dye or flavour (4), pot herb (4), salad (3), beverage (2), sauce (2), condiment (1), oil seeds (1), flatbread (1), sour (1), and tantur (1). Over 63.18% of sample households extracted and utilised all the forestry food resources extremely often for cash earnings and sustenance during the peak period. Forestry food resources constitute a key source of food, nutrition, health care, subsistence, cash income, and safety nets. This study gives insights to promote the conservation of forestry foods, develop management strategies that could be harmonised with rural development, poverty alleviation, food security, and livelihood sustainability for rural communities in Leh Himalaya, and accordingly design useful policy implications.